SOT-MTJ-based non-volatile flip-flop with in-memory randomness for application in grain stream ciphers - Nisar, Arshid (2025)
This paper proposes a method for in-memory true random number generation (TRNG) by leveraging the dual functionality of spin-orbit torque based magnetic tunnel junction (SOT-MTJ) while showcasing its efficacy in hardware-efficient Grain stream ciphers for lightweight cryptographic applications. Depending upon its mode of operation, SOT-MTJ acts as both a memory element and a true random number generator. To demonstrate its practical application, SOT-MTJ based non-volatile flip flop (NVFF) is designed which is further utilized to implement Grain-128 stream cipher, as a case study. The SOT-MTJ based NVFF not only carries out the standard shift operation for cipher implementation but also functions as an in-situ initial vector generator for generating key stream, eliminating the need for an additional TRNG circuit. The results show that the proposed Grain-128 cipher design is 5.6 × and 2.5 × more energy efficient and 5× and 2× faster as compared to STT and SOT-MTJ based designs. Furthermore, in comparison to CMOS based cipher design, the proposed technique shows nearly ∼34× more efficiency in terms of area overhead. The proposed approach holds huge promise for resource-constrained cryptographic applications in edge devices.